Influence of the surface chemistry in the osteogenic activity of silica nano particles - Amorim, Sara (2013)
Polyeletrolyte multilayers (PEM) have been extensively studied in the biomedical field, namely as biodegradable systems, biosensors and drug delivery systems [1]. Using PEM films, it is possible to control the early steps in cell adhesion but also processes that occur at a longer time scale, such as cell differentiation and tissue formation. In this work, we study the influence of silica particles concentration, coated with polyelectrolytes, and we evaluate their biological activity (osteogenic differentiation of human bone marrow stem cells - hBMSC) as a function of the nanoparticle’s concentration and surface coating. We chose to execute the polyelectrolyte constructions using poly-L-lysine (PLL), a polycation which is widely used in cell culture to promote cell adhesion to solid substrates [2], and hyaluronic acid (HA), a polyanion, which is known for providing excellent biocompatibility and have been used for ophthalmic surgery, treatment of arthritis, drug delivery, and tissue engineering [3]. In this context, we prepared silica nanoparticles (diameter of ~174nm) and silica particles coated with PLL-HA (diameter of ~200 nm). Further on, we studied the activity of these systems, under different concentration of particles (50µg/mL, 25µg/mL and 12,5µg/mL), towards the osteogenic differentiation of hBMSC. The cell viability, cell proliferation, protein quantification (i.e. ALP, DNA and MTS) and gene expression (evaluated by RT-PCR, i.e. Osteocalcin, Bone Sialoprotein, Runx2, Osteopontin and Osterix) was monitored, during 21 days. Our data indicates the overexpression of some of the osteogenic transcripts (e.g. Bone Sialoprotein, Osteocalcin and Osterix) in the hBMSCs cultured in the presence of SiO2-PLL-HA, under concentrations of 100µg/mL and 50µg/mL, in comparison with non-coated silica nanoparticles.